Evaluation of the Response of Posttensioned Steel Frames with Energy Dissipators Using Equivalent Single-Degree-of-Freedom Systems - J. Luz Rivera; Arturo López-Barraza; Sonia E. Ruiz; Alfredo Reyes-Salazar (Advances in Materials Science and Engineering)
The hysteretic energy (EH) dissipated in posttensioned steel frames (PTSF) with hysteretic dampers is calculated by using equivalent single-degree-of-freedom systems (ESDOFS), where the nonlinearity of both the steel bars (beam and columns) and the connections of the structural frame is separately considered. Five multi-degree-of-freedom (MDOFS) PTSF and their corresponding ESDOFS are studied under the action of 30 seismic motions recorded in soft ground, scaled in terms of the spectral pseudoacceleration evaluated at the fundamental period of the structures. Several simple mathematical expressions are proposed. The first expression is useful to calculate modifying factors (FMEH) to relate EH of the ESDOFS with that of the MDOFS; the second is to determine the interstory drift (γ) as a function of the seismic intensity. The third equation is to calculate the factor of the relative participation of the energy that the connections dissipate with respect to the total energy EH and the fourth equation, which is function of the γ, is to obtain the distribution factors of EH through the height of the structure. The methodology proposed can be used for the design or the structural revision of PTSF with dampers.